(untitled) (Research, Society and Development, 2022)
In recent years there has been a drop in childhood vaccination coverage in Brazil, including vaccination against polio, which increases the risk of reintroduction of poliovirus in the country. In this context, the study aimed to analyze the distribution, homogeneity and spatial autocorrelation of polio vaccine coverage and its correlation with sociodemographic indicators in the state of Paraná, Brazil. This is an ecological study with data from the SI-PNI from 2016 to 2020. The polio vaccine coverage and homogeneity were calculated. Spatial autocorrelation was analyzed by the Local and Global Moran Index. Pearson’s and Spearman’s correlation coefficients were used to verify the correlation between vaccination coverage and sociodemographic variables. Of the 399 municipalities in the state, only 54.6% had a vaccination coverage rate of 95% or more during the study period. The average homogeneity rate was 52.4% and low-low clusters were identified predominantly in the metropolitan mesoregion of the state. There was a weak correlation between vaccination coverage and sociodemographic variables. It is concluded that the state of Paraná has important differences in the distribution of vaccination coverage against poliomyelitis and a heterogeneity profile, which reinforces the need for strategies aimed at increasing vaccination coverage.